Milk Quality from Organic Farm - Veronica Wanniatie (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Nowdays, people prefer to consume safe and healthy food such as organic food and milk. Organic milk comes from organic farms applying sustainable environment and animal welfare. Consumers choose organic milk because it provides health benefits and comes from farm that applying animal welfare and green environment. Organic milk contains no pesticide residues, antibiotics and other contaminants. This paper describes the comparison of conventional and organic dairy farm and the quality of organic milk in terms of nutrition and contaminant. Organic farming that implements a production system for premium market with special requirements of production process and product quality, demands high management qualification. The difference between organic and conventional milk is the higher level of conjugated linoleic acid (CLA) because of rich forage feed in an organic livestock raising system.